Regional Differences in Metronidazole Resistance and Increasing Clarithromycin Resistance among Helicobacter pylori Isolates from Japan - Kato, Mototsugu (American Society for Microbiology, 2000)
The patterns of antibiotic resistance in Helicobacter pylori were assessed in two different regions in Japan. Overall, prevalences of resistance to metronidazole and clarithromycin were 12.4 and 12.9%, respectively. While there was no difference in clarithromycin resistance, the prevalence of metronidazole resistance was significantly higher in Kyoto (23.8%) than in Sapporo (8.1%). From 1996 to 1999, the prevalence of metronidazole resistance did not change but the prevalence of clarithromycin resistance doubled (from 9.1 to 18.7%).